Relativisme Budaya Bagi Masyarakat Multikultural Indonesia - Nurulaen, Yuyun (LP2M IAIN Palangka Raya, 2012)
Cultural relativism occurred in response to the flow of ethnocentrism, which holds that measure and assess the culture of others from their own cultural context, so it tends to look down on cultures outside the scope of culture.The basic concept of cultural relativism is not there a culture that has advantages compared with other cultures. Its means that there is no a community of people who are entitled to claim that their culture is superior to other cultures.Important cultural relativism learned by anyone who has a concern to the development of culture, both for development theory or to solve the problems that exist in the community, Indonesian society, especially the type of multicultural culture. Indonesia has a cultural diversity should be preserved and cultivated especially in the younger generation. to understand and be aware of the differences in terms of both religious cultures and races, Indonesian society should be able to live in diversity because it becomes a necessity.